Agent and web service technologies in virtual enterprises - Protogeros (Information Science Reference, 2008)
"This book provides a comprehensive review of the most recent advances in agent and Web service technologies. It provides an integrated view of the most recent contributions which support formation, integration, collaboration, and operation in virtual enterprise. Readers will gain insight from examples of applications of these technologies throughout various aspects of the virtual enterprise life cycle"--Provided by publisher.